Analisis Minat Penggunaan Ulang pada Dompet Digital Shopeepay di Masa Pandemi Covid-19 - Yola Auralia; Alfatih Sikki Manggabarani; Wahyudi Wahyudi (Studi Ilmu Manajemen dan Organisasi, 2020)
Purpose: The purpose of this study is to analyze and prove the influence of perceived usefulness, perceived ease of use and sales promotion on reuse intention the ShopeePay digital wallet during the Covid-19 pandemic. Research Methodology: This study is a quantitative research, the data in this research have been acquired form the distribution of questionnaires measured via ascale Likert using the Partial Least Square (PLS) technique which data processing was assisted by Smart PLS 3.3.3. In this research, a sample of 96 people was used, and the sampling technique used was the purposive sampling method. Result: The results of this research imply that the perceived usefulness variable has no effect and not significant on interest in reuse with a path coefficient value of 0.192. The variable perceived ease of use has a positive and significant effect on interest in reuse with a path coefficient value of 0.314 and sales promotion has a positive and significant effect on interest in reuse with a path coefficient value of 0.274. Limitations: Due to the Covid-19 pandemic, the spread of questionnaires must use Google Form (online) so that it cannot spread the questionnaire directly. And the variables used and set out in this study are limited i.e., refer only to the variables of benefit perception, ease perception and sales promotion. Contribution: It is expected to be able to share the contribution of knowledge and benefits and this writing can be a contribution as a source of reference and have the same topic, and can have the benefit to be a consideration for the company that it can be used as a consideration in determining strategies towards its product or service. Keywords: Reuse Intention, Perceived Usefulness, Perceived Ease of Use, Sales Promotion.